Solid-Liquid Phase Equilibrium: Alkane Systems for Low-Temperature Energy Storage - Sequeira, Maria C. M.; Nogueira, Bernardo A.; Caetano, Fernando J. P.; Diogo, Herminio P.; Fareleira, Joao M. N. A.; FAUSTO, RUI (Springer/Plenum Publishers, 2024)
The thermal characterization of two binary systems of n-alkanes that can be used as Phase Change Materials (PCMs) for thermal energy storage at low temperatures is reported in this work. The construction of the solid-liquid binary phase diagrams was achieved using differential scanning calorimetry (DSC) and Raman spectroscopy. The solidus and liquidus equilibrium temperatures were determined using DSC for thirty-nine different samples, three for the pure n-alkanes and the remaining for binary mixtures at selected molar compositions and used to acquire the corresponding solid-liquid phase diagrams. The two binary systems of n-octane/n-decane (C8/C10) and n-decane/n-dodecane (C10/C12) are characterized by a eutectic behavior at low temperatures. The eutectic temperature for the system C8/C10 was found at 211.95 K and the eutectic composition appeared at the molar fraction xoctane = 0.87. For the system C10/C12, the eutectic temperature was found at 237.85 K, and the eutectic composition appeared for the molar fraction xdecane = 0.78. This work aims to fulfill the lack of available data in the existing literature, considering the potential application of these systems for low-temperature thermal energy storage. Raman spectroscopy was used to complement the DSC data for the construction of the solid-liquid phase equilibrium diagrams, enabling the identification of the solid and liquid phases of the system. Additionally, the liquidus curve of the phase diagram was successfully described using a modified freezing point depression curve as fitting equation, the absolute root mean square deviation for the data correlation of the C8/C10 and C10/C12 systems being 2.56 K and 1.22 K, respectively. Ultimately, the fitting procedure also enabled a good prediction of the eutectic point for both studied systems.
Keywords: Alkanes; Binary Phase Diagram; Energy Storage; Eutectic; Phase Change Material (PCM)